Šiaurinių širvintiškių daiktavardžio kamienai ir jų hierarchija - Markevičius, Aurimas (Baltistica, 2006)
NOUN STEMS AND THEIR HIERARCHY IN THE NORTHERN ŠIRVINTIŠKIAI SUBDIALECT In the Northern Širvintiškiai subdialect, a noun stem is treated as independent if it differs from other stems in at least the ending of one case form. With regard to this condition, the i stem and the consonant stem are subdivided into the masculine and feminine gender stems. In the subdialect, traditional stems have been better retained in nouns having mobile stress. Due to shortening of unstressed long vowels, partial stress retraction and other reasons, barytone nouns have deviated to a great extent from the primary paradigms. In the Northern Širvintiškiai subdialect, the number of noun stems is lower than that in standard Lithuanian and in the majority of its dialects, as i̯u, i̯a1 and i̯a2 stem nouns are inflected in a totally homogeneous way, i. e. according to the i̯a2 stem implicative model. Nouns of mobile stress have a, i̯a2, u, ā, i̯ā, ē, im, if, Cm and Cf stems. Barytone stress nouns only have six stems, i. e. a, i̯a2, u, ā, ē, and if stems. The i̯ā stem has coincided with the ē stem. Meanwhile, the im, Cm and Cf stems are not found in words with barytone stress. Hierarchic stem grouping “trees” that are produced using three methods (the maximum, minimum and average methods) indicate existence of three different types of noun declension: the masculine model (embracing the a, i̯a2 and u stems), the feminine model (the ā and i̯ā stems) and the mixed model (the im, if, Cm and Cf stems). The ē stem is isolated: it embraces feminine gender nouns, yet according to declension there is a tendency towards the mixed declension type to a slightly greater extent. The a, i̯a2, ā, i̯ā and ē stems are stable. They do not decline or rarely decline from their implicative models, and have no additional (complementary) paradigms. They are all (except for the i̯ā stem) highly productive, open, constantly enriched with words from standard Lithuanian, other dialects and languages, and also with words having unstable stems. Unstable stems are as follows: u, im, if, Cm and Cf.They are unproductive, and often have complementary paradigms and lose part of words belonging to them.